Povezanost između polimorfizama gena IL-6 i rizika od osteoartritisa: sistematski pregled i meta-analiza: IL-6 Polymorphisms and Osteoarthritis Risk Meta-Analysis - Sun, Lichun; Zhao, Lian; Su, Lanfang; Wu, Qingjun; Jia, Bingshen; Zhang, Jing (Journal of Medical Biochemistry, 2026)
Background: This study systematically evaluates the association between interleukin-6 (IL-6) gene polymorphisms and osteoarthritis (OA) risk through a meta-analysis. Methods: Following PRISMA guidelines, a literature search was conducted in several databases, including studies published up to February 2025. Eligible studies included OA patients diagnosed by ACR criteria, investigating IL-6 gene promoter polymorphisms (rs1800795, rs1800797, rs1800798) and reporting genotype data or odds ratios (ORs) with 95% confidence intervals (CIs). Meta-analysis was performed using Stata 15.1, and subgroup analyses (ethnicity, OA subtype), and Egger’s test were conducted. Results: A total of 13 case-control studies (16 datasets) were included, covering three major IL-6 gene polymorphic sites: The 174 G/C (rs1800795) polymorphism showed no significant association with OA risk in overall or subgroup analyses (P > 0.05). The 572 G/C (rs1800797) polymorphism was significantly associated with a reduced OA risk under the dominant model (OR = 0.68, 95% CI: 0.48–0.97, P < 0.05), particularly demonstrating a protective effect in KOA. The 597 G/A (rs1800798) polymorphism showed no significant correlation with OA susceptibility (P > 0.05). Subgroup analyses confirmed result stability. Egger’s test detected no significant publication bias. Conclusion: IL-6 gene polymorphisms exhibit site- and population-specific effects on OA risk. The 572 G/C variant may confer protection against KOA. Further large-scale, multicenter studies are needed to validate these findings and explore underlying mechanisms for early OA diagnosis and personalized interventions.